Penggunaan Media Kartu Kata Bergambar dalam Menumbuhkan Minat Baca pada Anak di BiMBA AIUEO Margahayu Bekasi Timur - Luthfiah Azahra; Ahmad Junaedi Sitika; Debibik Nabilatul Fauziah (Pendidikan Agama Islam STIT Palapa Nusantara, 2022)
BiMBA AIUEO is an informal early childhood education institution aimed at guiding children's interest in learning. The picture word card media is a learning medium used in BiMBA AIUEO, the goal is for children to play while learning. This paper discusses the use of picture word cards in fostering children's interest in reading at BiMBA AIUEO Unit Margahayu East Bekasi. In this study the method used is descriptive qualitative, data collection in this study using observation, documentation and interview techniques. The results of the study show that the learning media applied at BiMBA AIUEO Margahayu East Bekasi Unit uses pictorial word card media with an individual system approach that is carried out by looking at the abilities of each child, using the small step system method, which is a method that focuses on children after seeing their abilities and also the application of the fun learning method which is a fun learning atmosphere activity. These methods are considered very effective in fostering interest in reading in children because they are in accordance with the world of children, namely playing while learning and learning while playing.